The massacre of the innocents studies in the cultural afterlife of a gospel scene - Carter, Warren 1955- (Lanham Lexington Books/Fortress Academic, 2023)
This book examines fifty instances from the afterlife of Matthew's "Massacre of the Innocents." Warren Carter argues that interpreters "think with" the scene's triad of power relations (tyrant, victims, means of tyranny) in various socio-political circumstances and media to make sense of these experiences and address their audiences.
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Chapter 1: Introduction -- Triad of Power Relations -- Narrative Sequence -- Thinking with Multiple Media and Genres -- Why Write This Study? -- Notes -- Part I: EARLY INTERPRETATIONS -- Chapter 2: Proto-Gospel of James -- Proto-Gospel of James -- Massacre of the Infants -- Thinking with the Matthean Scene -- Notes -- Chapter 3: Irenaeus -- Irenaeus Reads Matthew's Massacre -- Features -- Thinking with Matthew's Massacre -- Notes -- Chapter 4: Cyprian -- Conclusion -- Notes -- Part II: FIRST MILLENNIUM SERMONS -- Chapter 5: Chrysostom: Sermon 9 (d. 407) -- Preaching on the Massacre of the Innocents -- Herod the Angry -- "Did God Permit It?" -- Divine Foreknowledge? -- Rachel Weeps -- Thinking with Matthew's Massacre -- The Triad of Power Relations -- Notes -- Chapter 6: Chrysologus: Sermon 152 (d. 450) -- The Sermons -- Sermon 1525 Herod Condemned -- The Infants -- Christ -- The Infants Again -- Mothers -- Martyrdom -- Thinking with the Matthean Scene -- Notes -- Chapter 7: Quodvultdeus: Two Homilies on the Creed (430s CE) -- Occasion and Audiences -- Context and Invective -- The First Sermon on the Creed -- The Triad of Power Relations -- The Second Sermon on the Creed -- Thinking with the Massacre in the Second Sermon -- Conclusion -- Notes -- Chapter 8: Leo, Bishop of Rome (d. 461) -- Sermon 31 -- Sermon 32 -- Sermon 33 -- Sermon 35 -- Sermon 36 -- Sermon 37 -- Sermon 38 -- Conclusion -- Notes -- Chapter 9: Our Martyrs Are Better: A Fifth-Century Anonymous Sermon -- Sermon 11 -- Function of the Sermon -- Notes -- Chapter 10: Caesarius of Arles: Sermon 222, "On the Feast of the Holy Innocents" (d. 542) -- Sermon 222: On the Feast of the Holy Innocents -- The Sermon's Structure -- Infants as Martyrs -- Thinking with the Matthean Massacre -- Notes.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Prophecies; Bible.-Matthew, II, 16-18; MASSACRE of the Holy Innocents